Difficulties and Prospects for Non-Drug Treatment of Metabolic Syndrome in old Age - Baxramova Azima Abbosovna (American Journal of Biology and Natural Sciences, 2024)
Abdominal obesity (and the closely related metabolic syndrome) is one of the most common diseases in the world. The urgency of the problem of the progression of abdominal obesity lies not only in its widespread prevalence, but also in the formation of a high risk of developing cardiovascular diseases and type 2 diabetes mellitus.The main reasons for the rapid development of obesity are considered high-calorie nutrition (which includes not only the quantity, but also the quality of food eaten), a sedentary lifestyle and a genetic predisposition. Until now, there has been a heated debate about methods for fast and high-quality weight loss. There are many studies on the treatment of the various components of metabolic syndrome. Despite the many different pharmaceuticals developed for the treatment of abdominal obesity, non-drug methods of treatment and the organization of a healthy lifestyle come out on top, which is a difficult and, at times, overwhelming task for the clinician. One of the main reasons for failure in this field is the lack of time at the doctor for outpatient appointments. To address this issue, the role of the "Schools of Health" is considered in order to effectively reduce the body weight of patients with metabolic syndrome and maintain long-term results. A review of the prevalence and main causes of abdominal obesity is carried out, the results of existing schools in real clinical practice for the treatment of various chronic diseases are analyzed, an assessment of their effectiveness is given.